2018
DOI: 10.1097/prs.0000000000004021
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of the Adipose-Derived Stromal Cells during Angiogenesis and Adipogenesis after Cell-Assisted Lipotransfer

Abstract: The authors characterized the dynamic changes occurring in donor adipose-derived stromal cells and fat and recipient tissue by tracing these cellular components following cell-assisted lipotransfer. The authors' findings highlight the therapeutic value of cell-assisted lipotransfer in tissue transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 33 publications
3
35
1
Order By: Relevance
“…Further refinement in the “graft replacement” mechanism, was provided by Hong et al [ 97 ], who generated an animal model using two transgenic reporter mice expressing different fluorescent signals (DsRed and green fluorescent protein). Tracing experiments elucidated the dynamic changes of donor ASC, donor fat and recipient tissue.…”
Section: Clinical Approachmentioning
confidence: 99%
“…Further refinement in the “graft replacement” mechanism, was provided by Hong et al [ 97 ], who generated an animal model using two transgenic reporter mice expressing different fluorescent signals (DsRed and green fluorescent protein). Tracing experiments elucidated the dynamic changes of donor ASC, donor fat and recipient tissue.…”
Section: Clinical Approachmentioning
confidence: 99%
“…The second hypothesis states that ASCs can induce angiogenesis and adipogenesis by differentiating into endothelial cells and adipocytes [48]. To elucidate the fate and microenvironmental changes of fat, ASCs, and recipient tissue associated with CAL, the author generated an experimental animal model using two different transgenic reporter mice, and grafted both fat and ASCs expressing different fluorescent signals into wild-type mice [1]. Tracing analyses revealed that the donor ASCs participated in angiogenesis by differentiating into endothelial cells.…”
Section: Mechanismmentioning
confidence: 99%
“…Another factor that may contribute to the proangiogenic effect seen with lipotransfer into irradiated tissues is the inclusion of additional vessel-forming elements [ 56 ]. These include endothelial cells, pericytes, smooth muscle cells, and their progenitors capable of forming vascular cells and blood vessels.…”
Section: Autologous Lipotransfer To Regenerate Radiated Tissuesmentioning
confidence: 99%